2017
DOI: 10.1038/s41598-017-11383-x
|View full text |Cite
|
Sign up to set email alerts
|

Label-free and real-time monitoring of single cell attachment on template-stripped plasmonic nano-holes

Abstract: Leveraging microfluidics and nano-plasmonics, we present in this paper a new method employing a micro-nano-device that is capable of monitoring the dynamic cell-substrate attachment process at single cell level in real time without labeling. The micro-nano-device essentially has a gold thin film as the substrate perforated with periodic, near-cm2-area, template-stripped nano-holes, which generate plasmonic extraordinary optical transmission (EOT) with a high sensitivity to refractive index changes at the metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Metal nanostructures have been applied for the detection of biomolecules using their interactions such as antigen−antibody reactions, 16 DNA hybridization, 17,18 and the analysis of cell dynamics. 19 Hence, label-free biosensor chips have the potential to be applied in medical diagnosis, especially in point of care testing (POCT). 20,21 For POCT applications, it is desirable that determination be completed in visible light due to the inexpensive equipment requirement and highly sensitive visual examination.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal nanostructures have been applied for the detection of biomolecules using their interactions such as antigen−antibody reactions, 16 DNA hybridization, 17,18 and the analysis of cell dynamics. 19 Hence, label-free biosensor chips have the potential to be applied in medical diagnosis, especially in point of care testing (POCT). 20,21 For POCT applications, it is desirable that determination be completed in visible light due to the inexpensive equipment requirement and highly sensitive visual examination.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Label-free biosensing by metal nanostructures has been a focus area in the biosensor field due to its many advantages such as high sensitivity, inexpensive equipment, simple and easy operation, fast detection, and real-time monitoring capability. Metal nanostructures have been applied for the detection of biomolecules using their interactions such as antigen–antibody reactions, DNA hybridization, , and the analysis of cell dynamics . Hence, label-free biosensor chips have the potential to be applied in medical diagnosis, especially in point of care testing (POCT). , For POCT applications, it is desirable that determination be completed in visible light due to the inexpensive equipment requirement and highly sensitive visual examination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This detection scheme circumvents the tedious and costly molecular tagging and enables the elucidation of biomolecular interactions in a noninvasive and dynamic manner. Among various label‐free sensing platforms, optical biosensors are distinguished by their compatibility with physiological solutions, robust performance, and ability to perform quantitative detection . The recent advances in nanotechnology have inspired the development of extraordinarily improved optical biosensors based on photonic nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 11b shows the schematics of the cell and detection module and a resonance peak shift which was observed upon interactive binding of VEGF to the antibodies with a sensitivity of 145 pg/mL. In another study, (Tu et al 2017) demonstrated label-free cell monitoring of C3H10 and HeLa cells for understanding the cell kinetics of these two different cell types. A mathematical expression was used to fit the retarded growth function and deduce the difference in adhesion dynamics.…”
Section: Cell-cell Interactionsmentioning
confidence: 99%